Critical Policy Analysis: Investigating ‘Missing’ Values in the Lifelong Education System of South Korea - K.P. Joo; In Tak Kwon (Adult Education Research Conference, 2010)
This paper illustrates that ‘critical policy analysis’ (CPA) can uncover meaningful ‘missing’ values within the highly structured, centralized South Korean lifelong education policies and institutions.